Seasonal Distribution of the Fin Whale (Balaenoptera physalus) in Antarctic and Australian Waters Based on Passive Acoustics - Aulich, Meghan G.; McCauley, Robert D.; Miller, Brian S.; Samaran, Flore; Giorli, Giacomo; Saunders, Benjamin J.; Erbe, Christine (Frontiers in Marine Science, 2022)
The fin whale is listed as globally vulnerable, with ongoing threats to their population, yet little is known about the distribution and movements of the Southern Hemisphere sub-species, Balaenoptera physalus quoyi. This study assesses fin whale distribution in the Southern Hemisphere analysing acoustic recordings from 15 locations in Antarctic and Australian waters from 2002 to 2019. A seasonal acoustic presence of fin whales in Antarctic waters from late austral summer to autumn (February to June) with long-term, consistent annual usage areas was identified at the Southern Kerguelen Plateau and Dumont d’Urville sites. In comparison, limited vocal presence of fin whales was observed at the Casey site. In Australian waters, fin whales were seasonally present from austral autumn to mid-spring (May to October) on east and west coasts, with a decadal pattern of acoustic presence observed at Cape Leeuwin, WA. Two migratory pathways are identified, from the Indian sector of Antarctica to the west coast of Australia and from the Pacific sector of Antarctica to the east coast of Australia. The identified seasonal distributions and migratory pathways provide valuable information to aid in monitoring the recovery of this vulnerable sub-species. We suggest the identified distribution and dispersal from the Southern Kerguelen Plateau and Dumont d’Urville sites to the west and east coasts of Australia respectively, as well as the spatial separation between Antarctic sites, provide preliminary evidence of separate sub-populations of the Southern Hemisphere sub-species of fin whale.